Administrative Barriers - Influence on Port Management Operations: Array - Turcanu (Marcu), Andra Luciana; Gasparotti, Carmen Marilena (EuroEconomica, 2020)
This paper refers to the impact of the port management operations on the goods transshipped on the inland waterways. I proposed to analyze the administrative barriers and their impact on the level of goods transhiped. During the time more and more port operators state that the import/export/transit process it is hampered by a number of factors. External good practices, that might be beneficial for inland waterway in the Danube Region have been identified and described. The identified good practices can serve as examples to be used for the optimization of processes at the Danube inland waterway. The factors that influence the management of import- export operations in inland waterways and will be analyzed in this paper are: border Police, tax and customs; navigation/traffic control authorities; port authorities/administrations; waterway & canal administration; other relevant authorities imposing barriers.